Support Vector Machine Based on microRNA Expression Profiles to Predict Histological Origin of Ampullary Carcinoma: Case Report of a Patient Affected From Adenocarcinoma of the Papilla of Vater With Lynch Syndrome. Issue 4 (April 2016) - Tavano, Francesca; Copetti, Massimiliano; Piepoli, Ada; Carella, Massimo; Gentile, Annamaria; Burbaci, Francesca Paola; Fontana, Andrea; De Bonis, Antonio; di Mola, Fabio Francesco; di Sebastiano, Pierluigi; Andriulli, Angelo
Abstract : Abstract: Adenocarcinomas of Vater's papilla (PVAC) may originate from either the pancreatic duct or the intestinal epithelium. Conflicting data have been reported about the frequency of the 2 anatomical entities and their influence on patients' prognosis. To ascertain the anatomical origin of PVAC in a family member of a Lynch syndrome kindred, we searched for microRNA (miRNA) expression profiles on resected tumor specimens. The support vector machine was trained on our previous miRNAs expression data sets of pancreatic and colorectal tissue samples and used to classify the site of origin of the tumor in our patient. The support vector machine worked by contrasting the profiles of miRNAs in patients with pancreatic ductal and colorectal cancers to that of our patient, which was finally classified as pancreatic ductal adenocarcinoma accordingly to alterations of 55 miRNAs. The PVAC might be originated from ductal epithelium rather than from the intestinal mucosa of the papilla in the case at issue. Alteration of miR-548b-3p, miR-551a, miR-21, miR-92a, miR-let-7i, and miR-181a* emerged as potentially associated with cancer genetic susceptibility in PVAC. Abstract : Supplemental digital content is available in the text.